2020
DOI: 10.1002/mds.28217
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of Metabolic Abnormalities Related to PSP According to the MDS‐PSP Criteria

Abstract: It remains unclear whether the supportive imaging features described in the diagnostic criteria for progressive supranuclear palsy (PSP) are suitable for the full clinical spectrum. The aim of the current study was to define and cross-validate the pattern of glucose metabolism in the brain associated with a diagnosis of different PSP variants. A retrospective multicenter cohort study performed on 73 PSP patients who were referred for a fluorodeoxyglucose positron emission tomography PET scan: PSP-Richardson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…These patterns have been described based on qualitative interpretation and semiquantitative analysis using voxel-based analysis or principal component analyses with the estimation of spatial covariance patterns (i.e. metabolic connectivity) [33][34][35][36][37][38][39][40]. Cortical hypometabolism in temporooccipital and parietal regions has also been described in PD-MCI or PD patients that develop dementia at follow-up [33].…”
Section: Common Indicationsmentioning
confidence: 99%
“…These patterns have been described based on qualitative interpretation and semiquantitative analysis using voxel-based analysis or principal component analyses with the estimation of spatial covariance patterns (i.e. metabolic connectivity) [33][34][35][36][37][38][39][40]. Cortical hypometabolism in temporooccipital and parietal regions has also been described in PD-MCI or PD patients that develop dementia at follow-up [33].…”
Section: Common Indicationsmentioning
confidence: 99%
“…Even so, the simpler model based on PDRP and delta has a number of advantages. Unlike PDRP and PDCP, MSARP and PSPRP have not been extensively validated across centers and imaging platforms 33,34,48‐50 . This is particularly relevant in the rs‐fMRI domain in which PDRP and PDCP networks have recently been identified and validated, 6,39,44 whereas MSA‐ and PSP‐related networks analogous to those identified using FDG‐PET have yet to be characterized using this modality.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike PDRP and PDCP, MSARP and PSPRP have not been extensively validated across centers and imaging platforms. 33,34,[48][49][50] This is particularly relevant in the rs-fMRI domain in which PDRP and PDCP networks have recently been identified and validated, 6,39,44 whereas MSA-and PSP-related networks analogous to those identified using FDG-PET have yet to be characterized using this modality. Our preliminary results suggest that the stereotyped relationship between PDRP and PDCP can also be discerned using noninvasive rs-fMRI techniques, which are better suited for large-scale clinical trials and potential diagnostic use.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning PSP, however, there is still uncertainty regarding its usefulness in distinguishing PSP clinical variants. A previous study demonstrated that FDG-PET is a reproducible diagnostic tool for PSP-RS and PSP-P variants 68 .…”
Section: Neuroimaging and Biofluids Biomarkersmentioning
confidence: 98%